From Gut to Heart: The TMAO Breakthrough Changing Southeast Asia’s Cardiac Landscape - Mulijono, Dasaad (Cardiology and Cardiovascular Medicine, 2025)
Trimethylamine N-oxide (TMAO) has emerged as a novel biomarker implicated in the pathogenesis and progression of various cardiometabolic conditions, including coronary artery disease (CAD), stroke, type 2 diabetes mellitus, obesity/metabolic syndrome, chronic kidney disease, restenosis, and heart failure. Despite increasing global recognition of its clinical relevance, TMAO testing was not available in Indonesia until Bethsaida Hospital, under the leadership of Prof. Dasaad Mulijono, successfully established a partnership with Prodia, the only private laboratory in the country willing to invest in TMAO diagnostic technology. This article describes the implementation of TMAO testing at Bethsaida Hospital, evaluates its diagnostic and prognostic utility, and explores its role in monitoring adherence to a healthy plant-based diet (PBD). Bethsaida Hospital is also a national pioneer in using Drug-Coated Balloon (DCB) technology for coronary interventions. Ongoing research at the institution investigates the relationship between TMAO levels and dietary adherence among cardiac patients. Individuals with lower TMAO concentrations tend to exhibit a reduced restenosis rate following DCB procedures. Furthermore, patients who demonstrate regression of coronary plaques, particularly those adhering to a PBD, consistently exhibit low TMAO levels, supporting its potential as a surrogate marker for a favourable gut microbiota composition and dietary pattern. TMAO remains the only clinically available biomarker that indirectly reflects gut microbiota health in relation to dietary intake, particularly in individuals following a PBD. Its potential application in precision medicine holds promise for enhancing risk stratification, guiding therapeutic interventions, and improving long-term cardiovascular outcomes in patients with cardiometabolic disorders